The fungal UmSrt1 and maize ZmSUT1 sucrose transporters battle for plant sugar resources. Issue 6 (2nd May 2017) - Wittek, Anke; Dreyer, Ingo; Al‐Rasheid, Khaled A.S.; Sauer, Norbert; Hedrich, Rainer; Geiger, Dietmar
Abstract: The biotrophic fungus Ustilago maydis causes corn smut disease, inducing tumor formation in its host Zea mays . Upon infection, the fungal hyphae invaginate the plasma membrane of infected maize cells, establishing an interface where pathogen and host are separated only by their plasma membranes. At this interface the fungal and maize sucrose transporters, UmSrt1 and ZmSUT1, compete for extracellular sucrose in the corn smut/maize pathosystem. Here we biophysically characterized ZmSUT1 and UmSrt1 in Xenopus oocytes with respect to their voltage‐, pH‐ and substrate‐dependence and determined affinities toward protons and sucrose. In contrast to ZmSUT1, UmSrt1 has a high affinity for sucrose and is relatively pH‐ and voltage‐independent. Using these quantitative parameters, we developed a mathematical model to simulate the competition for extracellular sucrose at the contact zone between the fungus and the host plant. This approach revealed that UmSrt1 exploits the apoplastic sucrose resource, which forces the plant transporter into a sucrose export mode providing the fungus with sugar from the phloem. Importantly, the high sucrose concentration in the phloem appeared disadvantageous for the ZmSUT1, preventing sucrose recovery from the apoplastic space in the fungus/plant interface. Abstract : The corn smut fungus exploits the sugar resources of its maize host and negatively affects yield and food quality. At the plant/pathogen interface, maize and corn smut sucrose transporters battle for plant sugar resources. Here, a combination of biophysical studies and mathematical simulations was employed to analyze this 'arms race' between plant and fungus.